Регулювання режимів електроспоживання регіонів в дослідженнях та на практиці - Dryomin V.P.; Abramov V.A.; Moguilyuk A.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2002)
The brief review of the basic results and modern condition of the main directions is executed in the field of power consumption regime regulation, which is the main alternative to introduction of maneuverable capacities in power. Despite of huge scientific base in this area its practical realization does not solve all available problems. The main reason of this situation is an absence of stimulus at all levels. Therefore it is necessary to pay more attention to the organizational and legal base development together with technical tasks.